IMPLEMENTASI MANAJEMEN HUBUNGAN PELANGGAN PADA UMKM LUMINOUS FLORAL - Hasan, Golan; Heryanto, Heryanto; Yulianti, Rosa; Saputra, Antoni (Bussman Journal : Indonesian Journal of Business and Management, 2025)
This study aims to analyze the Customer Relationship Management (CRM) strategies implemented by Luminous Floral, a florist business that has been operating since January 2024. Amidst the increasingly competitive florist industry, this research evaluates the effectiveness of digital marketing and experiential marketing approaches in building customer loyalty. A qualitative case study approach was employed, with data collected through customer feedback, direct observation, and social media analysis. The CRM framework used encompasses three key aspects: customer acquisition, customer retention, and customer expansion. The findings are expected to provide a comprehensive understanding of the importance of personal, responsive, and digital customer relationship management in enhancing brand awareness and customer loyalty, particularly for micro, small, and medium enterprises (MSMEs) in the florist sector. These insights may also serve as a practical reference for MSME practitioners in designing adaptive and customer-oriented marketing strategies.